Similarity Solutions for Boundary Layer Flows on a Moving Surface in Non-Newtonian Power-Law Fluids - Grosan, T. S.; Pop, I.; Na, T. Y. (Technische Mechanik - European Journal of Engineering Mechanics, 2019)
A similarity analysis of the boundary layer flow caused by the motion of a semi-infinite flat sulface in a non-Newtonian power-law fluid at rest is made in this paper. These similar solutions fall into two categories: similarity solutions corresponding to steady boundary layers over moving surfaces and similarity solutions corresponding to unsteady boundary layers past moving flat surfaces, respectively. Except in the special case n = 1/2 (pseudoplastic) and n = 1 (Newtonian) fluids, solutions of the first category problems must be obtainednumerically. However, for the second category analytical solutions are possible for a large class of pseudoplasticfluids (n < 1), including the case of a Newtonianfluid (n = 1).